Dual-catalytic decarbonylation of fatty acid methyl esters to form olefins. Issue 55 (25th June 2018) - Fieser, Megan E.; Schimler, Sydonie D.; Mitchell, Lauren A.; Wilborn, Emily G.; John, Alex; Hogan, Levi T.; Benson, Brooke; LaPointe, Anne M.; Tolman, William B.
Abstract : The homogeneous dehydrative decarbonylation of fatty acid methyl esters (FAMEs) to form olefins is reported. Abstract : The homogeneous dehydrative decarbonylation of fatty acid methyl esters (FAMEs) to form olefins is reported. In order to facilitate cleavage of the unactivated acyl C–O bond of the alkyl ester, a one pot dual-catalytic directing group strategy was developed through optimization of the individual transesterification and decarbonylation reaction steps.